Маки: Стихотворения и поэмы / Г. М. Поженян ; худ. С. С. Федотов - Поженян Григорий Михайлович (Воениздат, 1981)
Экземпляры: (20191210) / Инвентарный номер: 1865 / Сис.шифр: Р2 / Авт.знак: П46 / ББК: Р2